Salinity resistance strategy of okra (Abelmoschus esculentus L. Moench) cultivars produced in Benin Republic - GOUVEITCHA, Baudouin; KPINKOUN, Julien; MENSAH, Armel; GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD (My University, 2021)
Salinity negatively influences the physiology and productivity of plants which develop different strategies to resist to this stress. This study aims to evaluate the implication of sodium (Na), potassium (K), proline and soluble sugars accumulation in salt resistance of okra local cultivars after two weeks exposure to 0, 30, 60, 90 and 120 mM NaCl concentrations. Results revealed that the aerial part growth reduction under salt stress was more accentuated in the salt sensitive cultivar Keleya than the salt resistant Yodana. Na+ accumulation in leaves was more accentuated in Keleya than Yodana whereas proline accumulation was more accentuated in both leaves and roots of Yodana than Keleya. K+ content decrease was more accentuated both in leaves and roots of Keleya than Yodana. Consequently, the decrease in ionic selectivity ratio (K/Na) was more accentuated in the salt sensitive cultivar Keleya than the salt resistant Yodana in both leaves and roots. Soluble sugars accumulation in leaves depends on the NaCl concentration. Results indicated that the relative salinity resistance of cultivar Yodana is associated with sodium ions exclusion from leaves, the maintaining of good accumulation of potassium ions and a good K+ /Na+ selectivity ratio, and the accumulation of high amounts of proline.
Keywords: Abelmoschus species; NaCl; sodium; potassium; soluble sugars; proline.